Effect of the lunar cycle on mental illness – A single-center retrospective observational study - Radhakrishnan,Sriramadesigan; Selvaraj,Arun; Sivakumar,Perarul; Kulothungan,Vasanth; Sathiyamoorthy,Preethi (Global Journal of Health Sciences and Research)
Objectives: In Shakespeare’s play “Othello,” the maid Emilia tells Othello that the moon has drawn too close to the Earth — and driven men insane. The notion that a full moon can elicit strong emotions, strange behavior, and even physical disease is not merely literary. Even now, it is a deeply held notion. The goal of this study was to determine the effect of the lunar cycle on the psychiatric presentation of individuals with schizophrenia, BPAD mania, and ATPD. Material and Methods: Case files of Schizophrenia, bipolar affective disorder (BPAD) mania and psychosis patients admitted in our hospital during full moon and new moon ± 3 days for the past 5 years will be included in the study. Name, age, sex, duration of admission, worsening of symptoms during full moon day and new moon day, any injectable given or not will be noted. These data will be collected from medical records. Telephonic verification of symptom worseness during full moon and new moon will be done. Results: Among 207 participants 74 patients had Schizophrenia, 91 patients had BPAD mania, 25 patients had ATPD and 17 patients had acute psychosis. The exacerbation of psychiatric symptoms, chemical restraints, and admission during phases of moon was statistically associated with lunar patterns in the study population. The rest of the socio-demographic factors, duration of admission, caregiver belief, and symptom worsening noted by caregiver were all not associated with mental illness during lunar phases which is in line with most reported literature in this area. Conclusion: There was an association between symptom exacerbations, chemical restraints, admission with different lunar phase. There was no association for sociodemographic details, duration of admission, caregiver belief on symptom worsening, symptom worsening noted by caregiver with different lunar phases.